Assessing the Ability of Chloroplast and Nuclear DNA Gene Markers to Verify the Geographic Origin of Jatoba (Hymenaea courbaril L.) Timber. (16th April 2018) - Chaves, Camila L; Degen, Bernd; Pakull, Birte; Mader, Malte; Honorio, Euridice; Ruas, Paulo; Tysklind, Niklas; Sebbenn, Alexandre M
Abstract: Deforestation—reinforced by illegal logging—is a serious problem in many tropical regions and causes pervasive environmental and economic damage. Existing laws that intend to reduce illegal logging need efficient, fraud resistant control methods. We developed a genetic reference database for Jatoba ( Hymenaea courbaril ), an important, high value timber species from the Neotropics. The data set can be used for controls on declarations of wood origin. Samples from 308 Hymenaea trees from 12 locations in Brazil, Bolivia, Peru, and French Guiana have been collected and genotyped on 10 nuclear microsatellites (nSSRs), 13 chloroplast SNPs (cpSNP), and 1 chloroplast indel marker. The chloroplast gene markers have been developed using Illumina DNA sequencing. Bayesian cluster analysis divided the individuals based on the nSSRs into 8 genetic groups. Using self-assignment tests, the power of the genetic reference database to judge on declarations on the location has been tested for 3 different assignment methods. We observed a strong genetic differentiation among locations leading to high and reliable self-assignment rates for the locations between 50% to 100% (average of 88%). Although all 3 assignment methods came up with similar mean self-assignment rates, there were differences for some locations linked to the level of genetic diversity, differentiation, and heterozygosity. Our results show that the nuclear and chloroplast gene markers are effective to be used for a genetic certification system and can provide national and international authorities with a robust tool to confirm legality of timber.